Forecast with judgment and models - Francesca Monti (National Bank of Belgium, 2008)
This paper proposes a simple and model-consistent method for combining forecasts generated by structural micro-founded models and judgmental forecasts. The method also enables the judgmental forecasts to be interpreted through the lens of the model. We illustrate the proposed methodology with a real-time forecasting exercise, using a simple neo-Keynesian dynamic stochastic general equilibrium model and prediction from the Survey of Professional Forecasters
Keywords: C32; C53; 330; forecasting; judgment; structural models; Kalman Filter; real time; Makroökonometrie; Prognoseverfahren; Allgemeines Gleichgewicht; Wirtschaftsprognose; Theorie; Schätzung; USA